Mainstreaming equitable decision-making under uncertainty at the Water User Association level using a reallocation model in the Western Cape, South Africa - Xoxo, Beauten Sinetemba (Rhodes University, Faculty of Science, Institute for Water Research)
This thesis demonstrates how uncertainty can be explicitly incorporated into equitable decision-making in ungauged basins to support fair water reallocation strategies among conflicting uses and reduce vulnerability to water shortages. First, a methodological framework is developed to collect the required socio-economic data. Second, a role-playing game (RPG) is developed in collaboration with stakeholders to increase awareness and assess the implications of different allocation strategies and stakeholder actions. Thirdly, a reallocation decision-support system (Water-Sharing Tool) with dam storage and uncertainty is tested to inform strategic water planning under dry conditions. The study was carried out in collaboration with stakeholders in the upper reaches of the Koue Bokkeveld, Western Cape, South Africa. The study area is a winter rainfall area with commercial farming activities targeting the domestic and cross-border markets. Irrigation from numerous farm dams and run-of-river extraction compete with in-stream environmental protection targets for streamflow. The study area can be described as resource-poor in terms of institutional capacity, with water management decisions taken individually at a farm level. The key water users are the environment, farmers, lifestyle farmers (residents), and weekenders. The farmer group has three sub-groups: corporate-owned farms, family-owned commercial farms, and downstream less well-resourced farmers. Results from the user risk profiles show that the least influential actors reside downstream and are more vulnerable to water shortages, which could be attributed to upstream developments and their productivity-driven nature. The thesis pulls together the socio-economic data, the information contributed by the stakeholders during the RPG, uncertain natural runoff estimates, and water demands. It evaluates these using the Water Sharing Model to map water users' vulnerability under four different management strategies and assesses equitable reallocation outcomes of the proposed strategies to different users. The magnitude and frequency of decision risks and the underlying uncertainty in the water supply are quantified. As expected, results suggest peak risks during months with the lowest streamflow, with negative implications for fruit production in the catchment. Results also showed the negative supply effects of upstream infrastructure development on downstream users and ecosystems. Game results with the farmers suggested different crop choices in dry periods between upstream and downstream farmers. Downstream farmers were surprisingly more willing to forego their dry season entitlements under water-sharing strategies that resulted in serious production losses upstream, prioritising social stability over their own profits. Farmers reflected on the game as an educational tool to enhance system understanding. The study confirms that decision-makers' understanding of the implications of water allocation decisions and the surrounding uncertainty is critical to meeting justice/fairness objectives.
Keywords: Water-supply Management; Water-supply -- South Africa -- Western Cape; Right to water -- South Africa -- Western Cape; Water Distribution; Water resources development -- South Africa -- Western Cape; Uncertainty (Information theory); Hydrology Statistical methods